Biosynthesis of CdS Quantum Dots Mediated by Volatile Sulfur Compounds Released by Antarctic Pseudomonas fragi - Gallardo-Benavente, Carla; Carrión, Ornella; Todd, Jonathan D.; Pieretti, Joana C.; Seabra, Amedea B.; Durán, Nelson; Rubilar, Olga; Pérez-Donoso, José M.; Quiroz, Andrés (Frontiers in Microbiology, 2019)
Previously we reported the biosynthesis of intracellular cadmium sulfide quantum dots (CdS QDs) at low temperatures by the Antarctic strain Pseudomonas fragi GC01. Here we studied the role of volatile sulfur compounds (VSCs) in the biosynthesis of CdS QDs by P. fragi GC01. The biosynthesis of nanoparticles was evaluated in the presence of sulfate, sulfite, thiosulfate, sulfide, cysteine and methionine as sole sulfur sources. Intracellular biosynthesis occurred with all sulfur sources tested. However, extracellular biosynthesis was observed only in cultures amended with cysteine (Cys) and methionine (Met). Extracellular nanoparticles were characterized by dynamic light scattering, absorption and emission spectra, energy dispersive X-ray, atomic force microscopy, transmission electron microscopy, X-ray diffraction and X-ray photoelectron spectroscopy. Purified QDs correspond to cubic nanocrystals of CdS with sizes between 2 and 16 nm. The analysis of VSCs revealed that P. fragi GC01 produced hydrogen sulfide (H2S), methanethiol (MeSH) and dimethylsulfide (DMS) in the presence of sulfate, Met or Cys. Dimethyldisulfide (DMDS) was only detected in the presence of Met. Interestingly, MeSH was the main VSCs produced in this condition. In addition, MeSH was the only VSCs which concentration decreased in the presence of cadmium (Cd) with all the sulfur sources tested, suggesting that this gas interacts with Cd to form nanoparticles. The role of MeSH and DMS on Cds QDs biosynthesis was evaluated in two mutants of the Antarctic strain Pseudomonas deceptionensis M1T: megL- (unable to produce MeSH from Met) and mddA- (unable to generate DMS from MeSH). No biosynthesis of QDs was observed in the megL- strain, confirming the importance of MeSH in QD biosynthesis. In addition, the production of QDs in the mddA- strain was not affected, indicating that DMS is not a substrate for the biosynthesis of nanoparticles. Here, we confirm a link between MeSH production and CdS QDs biosynthesis when Met is used as sole sulfur source. This work represents the first report that directly associates the production of MeSH with the bacterial synthesis of QDs, thus revealing the importance of different VSCs in the biological generation of metal sulfide nanostructures.